PERANAN PERHATIAN ORANG TUA DALAM MENSTIMULUS KECERDASAN KOGNISI ANAK - Nofi Maria Krisnawati (Hikmah: Journal of Islamic Studies, 2020)
Abstract The research on the role of parents in stimulating children cognitive intelligence aims to uncover parents attention to the children cognitive intelligence, namely the result of learning. It is a non-experiment qualitative research examined to 33 students the fourth grade in social sciences subject. The date is qualitatively and descriptively analysed. The result shows that parents attention influences the stimulus of children cognitive intelligence. It can be concluded from the result of student learning. The result is in line with calculated-t hypothesis greater than ttabel with dk = n-k = 33-2 =31 on significant level 0,05. A one-tailed test is 1.695 meaning t value (17,447) is greater than ttabel (1,695). It means Ho rejected. Therefore, the hypothesis is sound that parents attention contributes positively to the stimulus of children cognitive intelligence. It can be seen form the student result of learning. In other word, the more attention the parent give to the children, the better the result of children’s learning and vice versa. Abstrak Penelitian peranan perhatian orang tua dalam menstimulus kecerdasan kognisi anak bertujuan untuk mengetahui pengaruh perhatian orang tua terhadap kecerdasan kognisi anak yang berupa hasil belajar. Penelitian ini merupakan penelitian kuantitatif non experiment yang diujicobakan kepada 33 peserta didik kelas IV mata pelajaran IPS, sedangkan data dianalisis secara diskriptif kualitatif. Hasil penelitian menunjukkan perhatian orang tua mempengaruhi stimulus kecerdasan kognisi anak, dapat dilihat dari hasil belajar siswa IPS. Hal ini sesuai dengan pengujian hipotesis t hitung yang lebih besar dari ttabel dengan dk = n-k = 33-2 =31 pada taraf signifikansi 0,05 uji satu sisi adalah 1.695 yang berarti thitung (17,447) lebih besar dari ttabel (1,695) hal ini berarti Ho ditolak. Dengan demikian hipotesis penelitian terbukti kebenarannya bahwa Perhatian Orang Tua berpengaruh positif terhadap stimulus kecerdasan kognisi anak yang berupa hasil belajar siswa. Simpulannya bahwa adanya pengaruh perhatian orang tua dalam menstimulus kecerdasan kognisi anak, yang mana semakin tinggi perhatian orang tua, maka cenderung semakin tampak kecerdasan anak dari segi hasil belajarnya, sebaliknya semakin rendah perhatian orang tua maka semakin rendah pula hasil belajarnya.